2021
DOI: 10.1038/s41598-021-84795-5
|View full text |Cite
|
Sign up to set email alerts
|

Joint speed feedback improves myoelectric prosthesis adaptation after perturbed reaches in non amputees

Abstract: Accurate control of human limbs involves both feedforward and feedback signals. For prosthetic arms, feedforward control is commonly accomplished by recording myoelectric signals from the residual limb to predict the user’s intent, but augmented feedback signals are not explicitly provided in commercial devices. Previous studies have demonstrated inconsistent results when artificial feedback was provided in the presence of vision; some studies showed benefits, while others did not. We hypothesized that negligi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 60 publications
(39 reference statements)
0
21
2
Order By: Relevance
“…Additionally, the same compensatory behavior was observed in both studies, where subjects would strategically underreach with the wrist and compensate by overreaching with the elbow to minimize the distance to the target. Interestingly, while we showed no impact of sensory feedback on the average errors in the previous study 27 , amputee reaches in the present study demonstrated lower elbow and wrist biases with feedback available [Fig. 4a].…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Additionally, the same compensatory behavior was observed in both studies, where subjects would strategically underreach with the wrist and compensate by overreaching with the elbow to minimize the distance to the target. Interestingly, while we showed no impact of sensory feedback on the average errors in the previous study 27 , amputee reaches in the present study demonstrated lower elbow and wrist biases with feedback available [Fig. 4a].…”
Section: Discussioncontrasting
confidence: 78%
“…In our previous research, we explicitly considered the uncertainty of incidental visual feedback and provided non-amputee subjects with joint speed feedback, which signi cantly reduced the uncertainty of joint speed within a moving reference frame 26 . In a following study, we found that joint speed feedback reduced reaching errors after a perturbation to a 1 degree-of-freedom (DoF) myoelectric controller 27 , however these studies could not fully investigate the context of a person with amputation using myoelectric control. Proprioceptive organs including muscle spindles and Golgi tendon organs are activated differently in an amputated limb than they are in intact limb; agonist-antagonist muscles pairs stimulate these organs during movement 28 , but this pairing is generally absent from amputated limbs.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Second, a linear change in speed, as controlled by the ALC, may not relate to a linear increase in the speed of the prosthesis, making these differences in control signals further difficult to discern. It is possible that providing sensory feedback of the speed calculated from the control signals may help the pilot to better identify his prosthesis speed, or to adapt to changing conditions [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the control disturbance was implemented by multiplying the prosthesis control signal by a gain, unbeknownst to the subjects ( Figure 2 , “disturbance gain selection” block) ( Cipriani et al, 2014 ). Similarly to an approach implemented in Earley et al (2017) and Earley et al (2021) , the gain of the myoelectric signal was doubled or reduced by 33% at the beginning of a disturbed trial. When the gain was doubled (high-gain disturbance), the system became more sensitive with respect to the nominal condition and the same muscle contraction now generated a stronger myoelectric signal.…”
Section: Methodsmentioning
confidence: 99%